Regulatory mechanisms, expression levels and proliferation effects of the FUS-DDIT3 fusion oncogene in liposarcoma - Åman, Pierre; Dolatabadi, Soheila; Svec, David; Jonasson, Emma; Safavi, Setareh; Andersson, Daniel; Grundevik, Pernilla; Thomsen, Christer; Ståhlberg, Anders (The Journal of pathology, 2016)
Fusion oncogenes are among the most common types of oncogene in human cancers. The gene rearrangements result in new combinations of regulatory elements and functional protein domains. Here we studied a subgroup of sarcomas and leukaemias characterized by the FET (FUS, EWSR1, TAF15) family of fusion oncogenes, including FUS-DDIT3 in myxoid liposarcoma (MLS). We investigated the regulatory mechanisms, expression levels and effects of FUS-DDIT3 in detail. FUS-DDIT3 showed a lower expression than normal FUS at both the mRNA and protein levels, and single-cell analysis revealed a lack of correlation between FUS-DDIT3 and FUS expression. FUS-DDIT3 transcription was regulated by the FUS promotor, while its mRNA stability depended on the DDIT3 sequence. FUS-DDIT3 protein stability was regulated by protein interactions through the FUS part, rather than the leucine zipper containing DDIT3 part. In addition, in vitro as well as in vivo FUS-DDIT3 protein expression data displayed highly variable expression levels between individual MLS cells. Combined mRNA and protein analyses at the single-cell level showed that FUS-DDIT3 protein expression was inversely correlated to the expression of cell proliferation-associated genes. We concluded that FUS-DDIT3 is uniquely regulated at the transcriptional as well as the post-translational level and that its expression level is important for MLS tumour development. The FET fusion oncogenes are potentially powerful drug targets and detailed knowledge about their regulation and functions may help in the development of novel treatments.
Keywords: Protein Binding; transfekce; Gene Expression Regulation, Neoplastic; Protein Stability; RNA, Messenger; Half-Life; stabilita proteinů; Cell Line, Tumor; Cell Proliferation; posttranslační úpravy proteinů; Transfection; Transcription, Genetic; regulace genové exprese u nádorů; stabilita RNA; signální transdukce; myxoid liposarcoma; promotorové oblasti (genetika); fúzní onkogenní proteiny; Protein Processing, Post-Translational; Signal Transduction; mRNA stability; genetická transkripce; Time Factors; vazba proteinů; myxoidní liposarkom; Oncogene Proteins, Fusion; lidé; Liposarcoma, Myxoid; Biomarkers, Tumor; poločas; Humans; RNA Stability; Promoter Regions, Genetic; časové faktory; proliferace buněk; chimaeric transcript; nádorové buněčné linie; messenger RNA; nádorové biomarkery; fusion gene regulation